Integrated Supervision Center of Huaihua International Inland Port: The Feasibility and Essentiality - Xiaohui, Shu; Guang, Tian; Yangkuo, Li (Advances in Social Sciences Research Journal, 2024)
Building an integrated supervision center in Huaihua is feasible and essential because Huaihua City is at the center of the border regions of Hunan, Hubei, Chongqing, Guizhou, and Guangxi. In addition, it is a national transportation hub in China because of its distinctive geographic location, abundant resources and labor force. Due to the development of Huaihua International Inland Port, Huaihua has an excellent opportunity to be a logistics and trade center for inland areas in Central China. Given considerations in national strategies, food security, economic development and other factors, an integrated supervision center can be built in Huaihua, as it can promote the connectivity of the Wuling Mountain area and the neighboring provinces, contribute to regional economic development, and enhance China’s national security and supervisory capacity. The development of Huaihua as an integrated supervision center facilitates the processing, bonded warehousing and logistics distribution of high-quality imported commodities from neighboring countries, especially ASEAN countries.